Frequency of Oral Lesions and Its Relationship with Some Variables - MA Alaei Bakhsh (Babol University of Medical Sciences, 2021)
BACKGROUND AND OBJECTIVE: Early diagnosis of oral diseases affects the prognosis and treatment. Despite advances in oral health, there are still oral health problems worldwide. Considering that culture, gender, age, ethnicity and habits may have a significant impact on the prevalence of lesions, this study was performed to investigate the frequency of oral lesions over 10 years and its relationship with some variables. METHODS: In this cross-sectional study, the medical records of 1092 patients with various types of oral lesions who referred to the Department of Oral and Maxillofacial Diseases of Babol Dental School during 2009-2017 were evaluated and compared based on year, age, gender, type of lesion (white and red, pigmented, vesiculobullous, orofacial and tumoral pains, and disorders associated with systemic and peripheral or central diseases). FINDINGS: In this study, out of 1092 cases, 672 cases were related to female clients (61.5%) and 420 cases (38.5%) were related to male clients (p<0.001). The mean age of the subjects was 43.2±16.81 years. The highest frequency was related to white and red lesions with 305 cases (27.9%), which was 193 cases in women (28.7%) and 112 cases in men (26.7%) (p<0.001). The highest frequency of lesions was related to the cheeks with 351 cases (32.1%) including 235 cases (35%) in women and 116 cases (27.6%) in men (p<0.01). The lowest frequency was observed in the floor of mouth in 68 cases (6.2%). Tumoral lesions had a higher mean age of involvement than other lesions (p<0.001). The frequency of orofacial pain and burning symptoms in women was significantly higher than men (p=0.006). CONCLUSION: The results of the study showed that the frequency of white and red lesions of the mouth is more than other cases and its most common location is in the buccal mucosa. The frequency of lesions also has a significant positive relationship with female gender.